การนำเสนอแนวทางการจัดกิจกรรมพลศึกษาสำหรับเด็กออทิสติกที่มีระดับความสามารถปานกลางในโรงเรียนที่มีการจัดการเรียนร่วมในระดับประถมศึกษา PROPOSED GUIDELINES OF ORGANIZING PHYSICAL ACTIVITY FOR AUTISTIC CHILDREN WITH A MODERATE ABILITY LEVEL IN THE INCLUSIVE ... - คำจันทร์ เบญจพร; สมะวรรธนะ รุ่งระวี (An Online Journal of Education, 2017)
การศึกษานี้มีวัตถุประสงค์เพื่อ 1. ศึกษาสภาพปัญหาและความต้องการจำเป็นในการจัดกิจกรรมพลศึกษาสำหรับเด็กออทิสติกที่มีความสามารถในระดับปานกลาง 2. การนำเสนอแนวทางการจัดกิจกรรมพลศึกษาสำหรับเด็กออทิสติกที่มีความสามารถในระดับปานกลาง โดยกลุ่มตัวอย่างที่ใช้ในการวิจัยมี 4 กลุ่มได้แก่ ผู้บริหารและหัวหน้ากลุ่มสาระการเรียนรู้สุขศึกษาและพลศึกษา (42 คน) ครูพลศึกษา (42 คน) ครูการศึกษาพิเศษ (42 คน) และผู้ปกครอง (42 คน) จาก 14 โรงเรียน เครื่องมือวิจัยเป็นแบบสอบถามความคิดเห็น (ค่าความตรง 0.67 และความเที่ยง 0.98) และการสัมภาษณ์แบบ กึ่งโครงสร้าง ผลการวิจัยพบว่า 1) ด้านสภาพปัญหาการจัดกิจกรรมพลศึกษาและการจัดกิจกรรมบรรดิการทางพลศึกษา งบประมาณ และเครื่องมือสิ่งอำนวยความสะดวกสำหรับการจัดกิจกรรม อยู่ในระดับปานกลาง และมีความต้องการจำเป็นอยู่ในระดับมากในทุกรายการม 2) แนวทางการจัดกิจกรรมทางพลศึกษามีองค์ประกอบที่เกี่ยวข้องได้แก่ ด้านผู้บริหารและหัวหน้ากลุ่มสาระการเรียนรู้สุขศึกษาและพลศึกษาควรมีการจัดสรรงบประมาณที่เพียงพอต่อการจัดกิจกรรมพลศึกษา ด้านครูพลศึกษา ครูการศึกษาพิเศษควรเป็นผู้มีความรู้เฉพาะทาง และผู้ปกครองควรได้รับการจัดอบรมหรือการเข้าร่วมสัมมนาในเรื่องการจัดกิจกรรมสำหรับเด็กออทิสติก This study aimed to: 1) study the problems and needs of organizing physical education for autistic children with moderate ability; and 2) to propose guidelines of organizing physical education for autistic children with moderate ability. The samples in the research consisted of a group of chief executives learning in health and physical education. This group consisted of 42 people, physical education teachers 42 people, teacher special educators 42 people, and parents 42 people from 14 schools. The research instruments used were a questionnaire (validity, IOC = 0.67, reliability = 0.98), and a semi-structured interview. The result found that 1) the overall state of problems were at a high level, including providing adapted physical education activities, budget allocation of the facilities, state of the equipment, and the environment with activities for autism children. The schools need to provide individual planning, special educators and parents that are trained or attend a seminar on the subject of organizing activities for children with autism; and 2) the guidelines were composed of administrators supporting for budget and activity planning, the chief executive and group learning in health and physical education, Physical Education (PE) teachers and special educators need to be specialists in providing adapted PE activities, and parents should participate in the training and attend seminars with topics related to caring for autistic children.